St. Kitts and Nevis : 2017 Article IV Consultation- Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the economic performance of St. Kitts and Nevis moderated in 2016. Growth moderated, reflecting the deceleration in tourism-linked sectors and contraction in manufacturing output, while still exceeding the average growth in the Eastern Caribbean Currency Union region. Consumer inflation was negative, reflecting the favorable tax environment and low international fuel prices, but end-year inflation turned positive as these effects started to subside. Growth is expected to average at about 3 percent in the medium term. Inflation is projected to rise with the expected rise in fuel prices, remaining about 2 percent in the medium term.